Case Study of How Alleviating “Pebbles in the Shoe” Improves Operations in the Emergency Department - Diana Savitzky; Yash Chavda; Suchismita Datta; Alexandra Reens; Elizabeth Conklin; Matthew Scott; Christopher Caspers (Western Journal of Emergency Medicine)
Objectives: Addressing minor yet significant frustrations, or “pebbles,” in the workplace can reduce physician burnout, as noted by the American Medical Association. These “pebbles” are small workflow issues that are relatively easy to fix but can significantly improve the workday when resolved. This quality improvement project aimed to enhance clinician well-being in an emergency department (ED) affiliated with an academic institution through human-centered design by actively engaging clinicians to identify these “pebbles” and for a dedicated team to address them. Methods: A task force comprised of three emergency physicians collaborating with emergency medicine leadership was established. After educating clinicians about “pebbles,” clinicians were able to anonymously submit pebbles based on recall of frustrations in a baseline survey at the start of the project, as well as submit pebbles in real time by a QR code that was placed in easily noticeable areas. The task force met bimonthly to categorize, prioritize, and assign ownership of the pebbles. Progress was communicated to staff via a monthly “stop light” report. An anonymous survey assessed the impact on clinician well-being among 68 emergency clinicians within seven months of starting the project. Results: Over seven months, 284 pebbles were submitted (approximately 40 per month). The feasibility of addressing pebbles was characterized by a color scale: green (easy to fix): 149 (53%); yellow (more complex): 111 (39%); and red (not feasible, “boulder”): 24 (8%). Categories of pebbles included the following: equipment/supply: 115 (40%); nursing/clinical: 86 (30%); process: 64 (23%); and information technology/technology: 19 (7%). A total of 214 pebbles (75%) were completed. Among 51 respondents (75% response rate), the self-reported impact on well-being of having pebbles addressed was as follows: extremely effective: 16 (31%); very effective: 25 (49%); moderately effective: 8 (16%); slightly effective: 2 (4%); and not effective 0 (0%). Conclusion: In addition to improving personal resilience, improving well-being in the ED involves addressing efficiency of practice. This project highlights the positive impact of resolving small, feasible issues identified by clinicians, which resulted in 80% of respondents rating the project as very to extremely effective in improving their well-being. Most pebbles were related to equipment and easily fixed, while issues involving human interactions (eg, communications between consultants and EM) were more challenging. Regular meetings and accountability facilitated progress. This approach is replicable across medical specialties and practice settings, offering a low-cost method to enhance clinician work environments and well-being.